The Influence of Workplace Well-Being on Employee Turnover Intentions at Nusa Dua Beach Hotel & Spa - Darmawan, I Nengah Riky Agus; Sihombing, Irene Hanna H.; Witarsana, I Gusti Agung Gede (Institut Pariwisata dan Bisnis Internasional, 2023)
The high demands of work at hotels and the lack of employee well-being will have an impact on the emergence of intentional behavior and turnover intentions. Workplace Studentwell-being is one of the important factors that is thought to contribute to lowering the turnover intention at the workplace. When employee well-being in the workplace is fulfilled, then employees will feel comfortable and will give their best effort (peak performance) for the organization. The purpose of this research is to analyze how workplace well-being (X) can influence employee turnover intentions (Y) at the Nusa Dua Beach Hotel & Spa. This study uses a quantitative approach with a research tool using a questionnaire on the workplace well-being index and turnover intention. The number of subjects is 100, using the method of purposive sampling. Data analysis uses simple linear regression analysis with the help of the IBM SPSS application Statistic Version 25 For Windows. The results of the analysis that has been carried out show that workplace well-being has a significance score of 0.000 <0.05 and a Pearson correlation of (-0.473), which indicates that there is a significant negative direction of workplace well-being on turnover intention. The higher it is in workplace well-being, the lower will be turnover intention, even though the opposite is true if workplace well-being gets lower, the higher will be turnover intention.